Prolegomena to the metaphysics of Islam : an exposition of the fundamental elements of the worldview of Islam - al-Attas, Syed Muhammad Naquib, 1931- (Kuala Lumpur : International Institute of Islamic Thought and Civilization (ISTAC), 2001)
35